Water quality assessment based on saprobic index of phytoplankton with emphasis on several potentially Harmful Algal Blooms (HABs) - JABANG NURDIN; RIZKI AZIZ; LASTRI NUR; MUHAMMAD NAZRI JANRA (Society for Indonesian Biodiversity, 2025)
Abstract. Nurdin J, Aziz R, Nur L, Janra MN. 2025. Water quality assessment based on saprobic index of phytoplankton with emphasis on several potentially Harmful Algal Blooms (HABs). Biodiversitas 26: 890-899. The estuary is one of the most productive ecosystems on earth due to the accumulation of all materials, including nutrients, from the upstream to the downstream. This ecosystem also plays a role in habitat function for many living organisms, such as protists, bacteria, invertebrates, and vertebrates. However, this ecosystem may suffer from the accumulation of waste, which leads to pollution. This study aims to investigate and update the information regarding water quality based on the phytoplankton from the estuaries in Padang City, West Sumatra Province, Indonesia, and its potential as Harmful Algal Blooms (HABs). Sampling was conducted from November to December 2023 at six estuaries in Padang, and several formulas, such as diversity, equitability, dominance, Bray-Curtis, and saprobic indices, were used to analyze all of the data, respectively. A total of 130 species of phytoplankton belonging to five classes were identified, where Bacillariophyceae showed the highest diversity (98 species). Overall, the phytoplankton was moderate to highly diverse (2.95>=H' >=3.93), highly equitable (0.73>=EH>=0.93), low dominant species (0.03>=C>=0.11), and the highest similarity using Bray-Curtis occur between station 5 and station 6. At the same time, the Saprobic index was constant (X: 1.00). The pollution status at these estuaries could be considered light at the b-mesosaprobic or b-meso/oligosaprobic phase. In addition, 16 phytoplankton species were identified as HABs from these estuaries, including Alexandrium, Dinophysis, Prorocentrum, and Pseudo-nitzschia. Reducing the source of pollution from organic or non-organic materials, where the majority come from household waste disposal, may keep the health and quality of the rivers and estuaries in Padang